Antimicrobial use in cattle and poultry production on occurrence of multidrug resistant Escherichia coli. A systematic review with focus on sub-Saharan Africa - Azabo, Rogers; Dulle, Frankwell; Mshana, Stephen E.; Matee, Mecky; Kimera, Sharadhuli (Frontiers in Veterinary Science, 2022)
Antimicrobial use in livestock production has been linked to antimicrobial resistance (AMR) worldwide; however, optimization of their use has been considered an important strategy in dealing with it. The aims of this study were as follows: (a) to assess the literature on antimicrobial usage (practices, frequency, class, type) in cattle and poultry production with regard to resistance in Escherichia coli (E. coli) including multidrug resistance (MDR) (b) summarize evidence for quantitative (volumes of active antimicrobial ingredients) and quality (identify and quantify active ingredient) and (c) to identify data gaps. Peer reviewed literature search was conducted by querying two online databases: PubMed and Google scholar from November 15, 2018 to February 2019. The inclusion criteria for eligibility were articles: published in English between 2008 and 2018, including poultry (chicken) or cattle or both, E. coli bacteria of choice, antimicrobial use on farms, quantitative data and quality of antimicrobial used. Microsoft Excel was used for data extraction and Rayyan software for eligibility studies. The search retrieved 1,446 probable articles including those from the reference list of significant papers, of which twenty-four articles remained on full text review with more than a third of the studies being conducted in Nigeria. Farm surveys and antimicrobial sales were identified as the main sources of data and the mean quantities of antimicrobials based on sales data were 23,234, 41,280.87, and 1,538,443 kg of the active ingredient in Nigeria, Zambia and South Africa, respectively. One study from Cameroon determined the quantities of active ingredients based on dose metrics while another study still from Cameroon mentioned the quality of antimicrobials. Tetracyclines, beta-lactams/aminoglycosides and fluoroquinolones were the most common classes of antimicrobials (antibiotics) used. Our review reveals a dearth of information in Sub- Saharan Africa on the quantity and quality of veterinary drugs and yet they play a role in the overall picture of antimicrobial resistance. This finding gives an opportunity in the area of focus for future research as far as resistance and multidrug resistance are concerned in food producing animals.